Promotional effects of oxygen-containing additives on ammonia borane dehydrogenation for polymer electrolyte membrane fuel cell applications - Yeo, Shinyoung; Kim, Yongmin; Lee, Jin Hee; Kim, Kibeom; Jang, Jong Hyun; Hong, Seong-Ahn; Nam, Suk-Woo; Yoon, Chang Won (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
To develop continuous hydrogen generators utilizing ammonia borane (AB), one of the extensively studied chemical hydrogen storage material for applications in polymer electrolyte membrane fuel cells (PEMFCs), various types of oxygen-containing compounds such as 18-crown-6, 18-crown-6 derivatives, glycols, and polyethylene glycols were examined as chemical additives to enhance the H-2-release properties of AB. The rate and extent of AB dehydrogenation with these promoters were found to increase considerably at temperatures ranging from 85 degrees C to 125 degrees C; in particular, a mixture of AB and either 18-crown-6 or tetraethylene glycol afforded a material-based hydrogen storage capacity of >9.5 wt%. In situ Fourier transform infrared (FT-IR) and solid-state nuclear magnetic resonance (NMR) spectroscopic studies were conducted to identify gaseous byproducts potentially detrimental to a PEMFC. Density functional theory (DFT) studies demonstrated that the additives could interact with AB via hydrogen bonding between oxygen atoms of a promoter and N-H of AB, which could ultimately facilitate AB dehydrogenation. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CHEMICAL HYDROGEN STORAGE; THERMAL-DECOMPOSITION; METAL-FREE; RELEASE; HYDRIDES; COMPLEX; NMR